Elicitation of resistance responses in grapefruit and lemon fruits treated with a pomegranate peel extract. (28th August 2016) - Pangallo, S.; Li Destri Nicosia, M. G.; Raphael, G.; Levin, E.; Ballistreri, G.; Cacciola, S. O.; Rapisarda, P.; Droby, S.; Schena, L.
Abstract : The defence responses of grapefruit and lemon to treatment with pomegranate extract (PGE) were investigated. PGE, an alcoholic extract from pomegranate peel, was recently proposed as a means of effective alternative control against postharvest rots. In in vivo experiments, a significant reduction of rots caused by Penicillium digitatum and P. italicum was achieved on artificially inoculated fruits without direct contact between PGE and pathogens. On lemons both pathogens were completely inhibited by PGE at 12 g dry matter L −1 applied 12 and 24 h before the pathogen but a significant reduction of rots was also achieved by inoculating the pathogen immediately after PGE (0 h), indicating a very quick activation of defence responses. Lower, but significant, reductions were also obtained on grapefruits. An increase in reactive oxygen species (ROS) activity, reaching its peak after 24 h, was observed, in agreement with in vivo efficacy trials. Similarly, the expression of five genes involved in activation of defence responses in plants ( CHI, CHS, MAPK, MAPKK and PAL ) increased following PGE application. Based on the results of the present study, the high efficacy demonstrated for PGE in previous studies can be partially attributed to the induction of resistance in host tissues.